Aerodynamic measurements on a small HAWT rotor in axial and yawed flow - Bellia, J. M. (Cranfield University, 1990)
Current wind turbine performance codes are not yet able to predict the rotor aerodynamic behaviour with sufficient certainty. This has led to both the over-design of blades and to operational restrictions in certain wind conditions. Essentially the problem is one of aerodynamic stall. Steady 3-dimensional stall can occur near the blade root in high wind conditions and may produce more power than predicted. Dynamic stall can also be expected due to the effects of yawed operation, turbulence, tower shadow and the earth's boundary layer. The main aim of this work is to provide a coherent set of measured aerodynamic data accounting for both axial/non-axial flow and stall in high winds. These measurements are designed to highlight the effects of both steady and dynamic stall on the rotor aerodynamic performance. In addition, the data will enable current performance prediction codes to be developed and validated. A completely new turbine has been designed and built at Cranfield to make aerodynamic measurements using pressure transducers. The design has been dominated by the requirements of accommodating the transducer signal processing equipment and allowing variation of many of the rotor parameters. Three commercial glass fibre blades were installed and performance curves measured on a conventional field site at a height of 11.5m for three rotor speed settings. These measurements show the turbine to give adequate power performance. A mobile trailer has been used to tow the turbine at a height of 4m along the Cranfield runways. Mobile testing facilitates an accelerated test schedule and allows aerodynamic data to be acquired under controlled wind conditions. A fully instrumented blade, fitted with forty transducers, has been tested under these circumstances and produced a large database of pressure measurements covering operation in winds up to 25 iq/s and yaw angles between -4511 and +55°. Analysis of the data has shown it to be of good quality and allowed some of the effects of yaw and stall to be identified. The use of the data base for performance prediction code validation has also been established.